2002
DOI: 10.1001/archpedi.156.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Urine Testing and Urinary Tract Infections in Febrile Infants Seen in Office Settings

Abstract: Practitioners order urine tests selectively, focusing on younger and more ill-appearing infants and on those without an apparent fever source. Such selective urine testing, with close follow-up, was associated with few late UTIs in this large study. Urine testing should focus particularly on uncircumcised boys, girls, the youngest and sickest infants, and those with persistent fever.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
110
1
6

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 145 publications
(123 citation statements)
references
References 29 publications
6
110
1
6
Order By: Relevance
“…This fi nding confi rms previous studies suggesting that children with bacteremic UTI show no major clinical differences from those with nonbacteremic UTI at presentation. 6,9,10,20 Bacteremic infants were no more likely to have abnormal urinary imaging results. However, selective ordering of urinary imaging may have biased this fi nding.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This fi nding confi rms previous studies suggesting that children with bacteremic UTI show no major clinical differences from those with nonbacteremic UTI at presentation. 6,9,10,20 Bacteremic infants were no more likely to have abnormal urinary imaging results. However, selective ordering of urinary imaging may have biased this fi nding.…”
Section: Discussionmentioning
confidence: 97%
“…Our fi nding that the risk of bacteremia with UTI is inverse to age and quite low beyond 6 months confi rms previous results. 6,8,20,21 There are no published recommendations for a threshold pretest probability at which to obtain a blood culture in an infant with suspected UTI. Theoretically, the detection of bacteremia may be benefi cial if the extended hospitalizations and courses of parenteral antibiotics prevent a complication such as meningitis or recurrent UTI.…”
Section: Discussionmentioning
confidence: 99%
“…These benefits are not known and probably are not uniform; the younger and sicker an infant is and the longer he or she has been febrile, the greater the likely benefit of diagnosing and treating a UTI. Because acute symptoms of most UTIs seem to resolve un-eventfully, even without treatment, 5,6 some of the impetus for diagnosing UTIs rests on the belief that doing so will reduce the risk of renal scarring and associated sequelae. 7 This belief needs to be proven, and the benefit quantified, if a urine-testing threshold is to be evidence-based.…”
Section: Which Children Should Have Their Urine Tested?mentioning
confidence: 99%
“…12 Studies on variation and adherence to existing practice guidelines for evaluation and management of fever in young infants have been limited to surveys or adherence to recommended urine testing or have excluded neonates 0-28 days of age. [13][14][15] Belfer et al 16 conducted a survey-based study on compliance with guidelines for the management of febrile infants and found 54% compliance among pediatric emergency medicine directors. To our knowledge, no large multi-institutional study has reported actual practice for the management of febrile neonates in terms of variation and adherence to standard recommendations in pediatric emergency departments (PEDs) in the United States.…”
mentioning
confidence: 99%